Criação, bioecologia e controle químico de spodoptera eridania (cramer) (lepidoptera : noctuidae) em soja. - Tibola, Cristiane Maria (2011)
In recent years, the occurrence of worms of the genus Spodoptera has been reported in soybean crops, causing severe damage to crops. The species S. eridania is a polyphagous insect, widely distributed in Brazil, which can be found in cultivated plants and weeds. Information on bio-ecological aspects and control of this insect in soybeans is incipient. Hence, ten experiments were conducted in order to adjust the rearing technique in laboratory aimed at the production of S. eridania, studying the basic aspects of bioecology of the species and assessing the potential of insecticides in the control of worms in soybean crops. Greene artificial diet proved to be suitable as feeding substrate for worms, individualized in glass containers, to rear S. eridania under laboratory conditions. Sunflower, soybean and Ipomoea sp. leaves were the most suitable for the development of S. eridania, among the seventeen plant species evaluated. The consumption capacity of S. eridania worms is three times greater than that of A. gemmatalis, in soybean leaves The location of the S. eridania larvae in the whole plant-soil varies throughout the day, which remain in the soil during the hottest hours, and on the plant, feeding in times during the night until early morning. Insecticides chlorantraniliprole, chlorantraniliprole + lambdacyhalothrin, chlorpyrifos, flubendiamide, lufenuron, lufenuron + profenofos, methomyl, methoxyfenozide, novaluron, teflubenzurom and triflumuron, sprayed in the aerial part of soybean plants, showed control efficiency exceeding 85%. Insecticides carbosulfan, fipronil, imidacloprid and thiamethoxam in the doses applied in seed treatment did not deliver effective protection of soybean seedlings in relation to the attack of the S. eridania larvae.